Etnohermeneutika Ki Hajar Dewantara tentang Nalar Islam Nusantara - Chafid Wahyudi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
The lack of wholeness in photographing Ki Hajar Dewantara put historicity as part of â€œMuslim Kejawenâ€ and syncretic. A kind of conclusion canâ€™t be separated from the production of knowledge anthropologists. This Conclusion is their attempt to make sense of the phenomenon of Islamic religious culture Java limited factual observations. Instead, the intersection itself with the universe to deliver Ki Hajar Dewantara reflect Sufi epistemology. Not stopping there and lived Islam impregnated for later conceptualized by Ki Hajar Dewantara not be separated from the acceptance of the culture. Methodological conceptualization of Islam Ki Hajar Dewantara is the actualization of methodological etnohermeneutis, which interprets religion (read: the word of God) in ways that are best understood from the Weltanschauung (world view) community recipients.Keywords: Sufism, Culture, Islam, Etnohermeneutics.